The anti MRSA biofilm activity of Thymus vulgaris essential oil in nanovesicles - Perez, Ana Paula (2019)
Background: Thymus vulgaris essential oil (T) could be an alternative to classical antibiotics against bacterial biofilms, which show increased tolerance to antibiotics and host defence systems and contribute to the persistence of chronic bacterial infections. Hypothesis: A nanovesicular formulation of T may chemically protect the structure and relative composition of its multiple components, potentially improving its antibacterial and antibiofilm activity. Study design: We prepared and structurally characterized T in two types of nanovesicles: nanoliposomes (L80-T) made of Soybean phosphatidylcholine (SPC) and Polysorbate 80 (P80) [SPC:P80:T 1:0.75:0.3 w:w], and nanoarchaeosomes (A80-T) made of SPC, P80 and total polar archaeolipids (TPA) extracted from archaebacteria Halorubrum tebenquichense [SPC:TPA:P80:T 0.5:0.50.75:0.7 w:w]. We determined the macrophage cytotoxicity and the antibacterial activity against Staphylococcus aureus ATCC 25,923 and four MRSA clinical strains. Results: L80-T (Z potential −4.1 ± 0.6 mV, ∼ 115 nm, ∼ 22 mg/ml T) and A80-T (Z potential −6.6 ± 1.5 mV, ∼ 130 nm, ∼ 42 mg/ml T) were colloidally and chemically stable, maintaining size, PDI, Z potential and T concentration for at least 90 days. While MIC 90 of L80-T was > 4 mg/ml T, MIC 90 of A80-T was 2 mg/ml T for all S. aureus strains. The antibiofilm formation activity was maximal for A80-T, while L80-T did not inhibit biofilm formation compared to untreated control. A80-T significantly decreased the biomass of preformed biofilms of S. aureus ATCC 25,923 strain and of 3 of the 4 clinical MRSA isolates at 4 mg/ml T. It was found that the viability of J774A.1 macrophages was decreased significantly upon 24 h incubation with A80-T, L80-T and T emulsion at 0.4 mg/ml T. These results show that from 0.4 mg/ml T, a value lower than MIC 90 and the one displaying antibiofilm activity, with independence of its formulation, T significantly decreased the macrophages viability. Conclusion: Overall, because of its lower MIC 90 against planktonic bacteria, higher antibiofilm formation capacity and stability during storage, A80-T resulted better antibacterial agent than T emulsion and L80-T. These results open new avenues to explode the A80-T antimicrobial intracellular activity.